(untitled) (Global Journals of Research in Engineering, 2012)
Expert Systems have been used to solve complex problems efficiently if the information available is in descriptive form rather than numbers. The study has aimed to use Fuzzy expert systems to estimate the labor production rates. Production rate values of formwork installation of beam have been measured from the project sites and factors influencing the production rates have been recorded on scale in descriptive form. Fuzzy expert system developed in this study has been compared with the previous Fuzzy expert systems used for estimating production rates. Mean Square Error of the previous and new models has been calculated and shows that proposed model gives high linguistic and numerical accuracies. Hence, the Fuzzy expert system developed in this study can be used reliably for estimating labor productivity by the construction Industry.